The State and Capitalism in China - Pearson, Margaret M.; Rithmire, Meg; Tsai, Kellee (Cambridge University Press, 2024)
China's contemporary political economy features an emboldened role for the state as owner and regulator, and with markets expected to act in the service of party-state goals. This Element situates China's political economy in comparative analytic perspective with attention to adaptations of its model over time.